Vpliv kavitacije na karakteristike črpalke v treh kvadrantih - Tarman, Peter (Acta hydrotechnica, 2000)
A pumping station must be designed not only for steady state flow conditions, but also for transient conditions. In order to analyze these phenomena, the pump characteristics in at least three quadrants are needed. The three quadrant pump characteristics can be known exactly only by testing on a test rig. When testing characteristics, it is important to provide similar cavitation conditions as those foreseen in a pumping station. Therefore, the paper discusses the cavitation influence on three quadrant pump characteristics, particularly focusing on energy dissipation. It is shown that cavitation in the impeller could be present during transient conditions (shut down of a pump) and effects on the pressure fluctuations within the pipeline
Keywords: cavitation in three quadrants; črpalke v treh kvadrantih; črpalno področje; energy dissipation zone; karakteristike; kavitacija v treh kvadrantih; prehodni režimi; pumping zone; three quadrant pump characteristics; transient conditions; turbine zone; turbinsko področje; vodni udar; water hammer; zavorno področje